(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The thesis "The Role of Financial Control in the Business Sector" provides a comprehensive analysis of how effective financial control systems impact the financial stability, transparency, and overall efficiency of business enterprises. The research delves into the theoretical foundations and modern approaches to financial control, examining its integral role within corporate governance structures. It evaluates various models and practices of financial control across different business sectors, highlighting their influence on fraud prevention, error detection, and risk mitigation. The study further explores the correlation between robust financial control mechanisms and key financial performance indicators such as profitability, liquidity, and solvency. By incorporating case studies and empirical data, the thesis underscores the advantages of leveraging advanced information technologies and automated systems in enhancing financial control processes. The findings suggest that businesses with well-implemented financial control frameworks exhibit improved decision-making capabilities, greater investor confidence, and increased market competitiveness. Recommendations are provided for optimizing financial control practices to bolster financial security and support sustainable business growth in a dynamic regulatory environment.